ZEBRAFISH AS AN EXPERIMENTAL MODEL FOR STUDIES ON BIOATIVE COMPOUNDS AND PROTEOMIC OF PLANTS: A REVIEW - Júnior, Zenon Ratzlaff; Houssaini, Mara Lisiane Tissot-Squalli (Salão do Conhecimento, 2018)
Work developed during the discipline Methodology of Biological Research, under graduation course of Biological Sciences of the Regional University of the Northwest of the State of Rio Grande do Sul - UNIJUÍ